A Conflicting Case of Strangulation: A Case Report - Wakde , S D (Journal of Indian Academy of Forensic Medicine, 2014)
A female aged 25 year was brought with a history of found unconscious at home, the body was sent to Government Medical College and Hospital, Aurangabad, Maharashtra for a medico legal post mortem. Deceased was having a ligature mark over anterior aspect of neck suggesting it as a case of hanging accompanied by few external injuries like abrasions over face and chest consistent with fall at ground level. On conclusion of autopsy, the cause of death was found to be strangulation. The process of strangulation, whether by hand (manual) or by ligature, results in blunt force injury of the tissues of neck. The pattern of these injuries allow us to recognize strangulation as a mechanism , and to distinguish strangulation from other blunt injuries including hanging, traumatic blows to the neck, and artifacts of decomposition. These classical finding were absent in this case. Absence of these characteristic findings could easily misinterpret such a case as that of hanging. Therefore I am presenting this case.